ANALYSIS STUDENTS’ SCIENCE PROCESS SKILLS IN SENIOR HIGH SCHOOL PRACTICUM BASED ON SMALL SCALE CHEMISTRY (SSC) - Harta, Johnsen; Pamenang, Fransisca Ditawati Nur; Listyarini, Risnita Vicky; Wijayanti, Lucia Wiwid; Hapsari, Natalia Diyah; Ratri, Monica Cahyaning; Asy'ari, Maslichah; Lee, Wonkoo (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Experiment is integral part of chemistry. Through experiments, everyone can verify and or find something new as an alternative solution to attract interest in meaningful chemistry learning. Innovative experimental packaging can be done with Small Scale Chemistry (SSC) to establish the importance of understanding and application related to the use of small amounts of reagents and reduce waste produced during chemistry practicum. This study aims to explore and analyze the science process skills of the second semester students of Chemistry Education Study Program, Sanata Dharma University, which focused for chemistry grade 12 in water electrolysis using straws and mini test tubes as physical chemistry’s experiment and formation reaction of silver mirror uses vial bottle and mirror media as experiment of organic chemistry. The results show that students’ science process skills which includes observation skills with good average score, prediction skills with good enough average score, skills in interpreting data with good average scores, and communication skills with good average score for two kind of experiments conducted. In general, students were enthusiastic in carrying out the two SSC experiments. The students also evaluate the experiments to be able to help develop and improve their soft skills in chemistry learning. Keywords: science process skills, senior high school practicum, small scale chemistry